PELATIHAN DAN UPDATING KODING KLINIS UNTUK KEPERLUAN REIMBURSEMENT KLAIM INA-CBGs PADA RUMAH SAKIT SWASTA - Ernawati, Dyah; Agiwahyuanto, Faik; Yulianah, Sri; Prasetya, Jaka; Muzakki Syah, Rizka (Indonesian Journal of Health Information Management Services, 2025)
Case-mix coding is a critical task for hospital staff, especially those in the medical records department and the case-mix unit responsible for managing JKN patient claims. To ensure accuracy in INA-CBGs reimbursement claims, training and skill development in clinical coding are essential. The UDINUS Community Service Team conducted a comprehensive training program involving knowledge sharing, interactive discussions, and practical mentoring on clinical coding enforcement and reimbursement processes. The training covered basic clinical coding concepts, application of ICD-10 and ICD-9CM standards, case analysis aligned with reimbursement regulations, hands-on coding practice, and concluded with a post-test. A total of 54 participants from diverse healthcare roles including medical record officers, doctors, nurses, and non-health personnel actively engaged in the sessions. Evaluation results indicated significant improvement in participants’ understanding of medical terminology and their ability to accurately apply clinical codes according to established guidelines. Additionally, the training highlighted the importance of clinical coding for effective hospital case-mix management. In summary, proficiency in medical terminology is vital for medical record officers to ensure precise clinical code assignment that supports high-quality health information data within healthcare institutions.